The effect of social media on investment capital development of transportation infrastructure - Thanh Thuy Cu; Thi Hoai Huong Hoang; Van Phuc Nguyen; Thi Yen Le (International Journal of Data and Network Science, 2022)
This study was designed to analyze the role of social media marketing in attracting investment capital from enterprises in the development of transport infrastructure in Vietnam. A survey of 378 Vietnamese companies operating in the sector of transport infrastructure investment was collected to compile these statistics. Based on the collected data, the factor analysis method and multivariate regression method are used to analyze the influence of factors on attracting development investment capital for transport infrastructure in Vietnam. The results of this study show that social media marketing had the greatest influence on firm satisfaction when investing in transport infrastructure; the Standardized Coefficient of the Social Media Marketing variable is 0.392. Based on that finding, some solutions to further enhance the value of social media marketing are recommended to increase the attraction of investment capital for the development of transport infrastructure in Vietnam.